AQSAM AL-QUR’AN: FUNGSI RETORIS DAN TEOLOGIS SUMPAH DALAM PENGUATAN HUJJAH WAHYU - Hamzah Tacong (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article examines the phenomenon of the aqsam (oath) in the Qur'an as a crucialelement in conveying theological and rhetorical messages of revelation. In numerous verses,Allah swears by His various creations to affirm the truth of His message, the oneness of God(tawhid), and the certainty of the Day of Judgment. This study is motivated by the importanceof understanding the function of oaths not only as a figure of speech but also as a powerful andprofound da'wah communication strategy. This research uses a qualitative descriptiveapproach through a literature review of verses containing oaths and classical andcontemporary interpretations of these verses. The results show that the aqsam not onlystrengthens the hujjah or divine argument but also shapes the emotional and spiritualresponses of its readers, particularly during the time of the Prophet Muhammad (peace beupon him), when the language of oaths possessed high suggestive and rhetorical power. Thediscussion demonstrates that the structure of oaths in the Qur'an contains theological,philosophical, and pedagogical meanings that can deepen the understanding of the divinemessage. Thus, the aqsam in the Qur'an becomes both a rhetorical instrument and an effectivemeans of preaching, instilling faith and submission to revelation.